Enhancement of CO2 uptake and selectivity in a metal-organic framework by incorporation of thiophene functionality - Bolotov, Vsevolod A.; Kovalenko, Konstantin A.; Samsonenko, Denis G.; Han, Xue; Zhang, Xinran; Smith, Gemma L.; McCormick, Laura; Teat, Simon J.; Yang, Sihai; Lennox, Matthew J.; Henley, Alice; Besley, Elena; et al. (American Chemical Society, 2018)
The complex [Zn2(tdc)2dabco] (H2tdc = thiophene-2,5-dicarboxylic acid; dabco = 1,4-diazabicyclooctane) shows a remarkable increase in CO2 uptake and CO2/N2 selectivity compared to the non-thiophene analogue [Zn2(bdc)2dabco] (H2bdc = benzene-1,4-dicarboxylic acid; terephthalic acid). CO2 adsorption at 1 bar for [Zn2(tdc)2dabco] is 67.4 cm3 x g–1 (13.2 wt.%) at 298 K and 153 cm3 x g–1 (30.0 wt.%) at 273 K. For [Zn2(bdc)2dabco] the equivalent values are 46 cm3 x g–1 (9.0 wt.%) and 122 cm3 x g–1 (23.9 wt.%), respectively. The isosteric heat of adsorption for CO2 in [Zn2(tdc)2dabco] at zero coverage is low (23.65 kJ x mol–1), ensuring facile regeneration of the porous material. The enhancement by the thiophene group on the separation of CO2/N2 gas mixtures has been confirmed by both ideal adsorbate solution theory (IAST) calculations and dynamic breakthrough experiments. The preferred binding sites of adsorbed CO2 in [Zn2(tdc)2dabco] have been unambiguously determined by in situ single crystal diffraction studies on CO2 loaded [Zn2(tdc)2dabco], coupled with quantum chemical calculations. These studies unveil the role of the thiophene moieties in the specific CO2 binding via an induced dipole interaction between the CO2 and the sulfur center, confirming that enhanced CO2 capacity in [Zn2(tdc)2dabco] is achieved without the presence of open metal sites. The experimental data and the theoretical insights suggest a viable strategy for improvement of adsorption properties of already known materials through incorporation of S-based heterocycles within their porous structures.